Frequency of Developmental Hip Dysplasia in a Training Hospital - Emrah Can; İlhan Asya Tanju; Cihan Meral (Haseki Tıp Bülteni, 2010)
Aim: We aimed to determine the frequency of cases with developmental hip dysplasia during the neonatal period and the associated risk factors. Methods: Hip ultrasound images of 258 full-term newborns aged one month were evaluated prospectively in conjunction with physical examination for developmental hip dysplasia in GATA well baby outpatient clinic. Results: The incidence of developmental hip dysplasia was 0.3% in one-month-old, healthy, full-term babies included in the study. 44% of them were male and 56% were female. The mean birth weight was 3311.8±511.4 g. 48% of all births were spontaneous vaginal deliveries and 52% cesarean deliveries. A history of oligohydramniosis was present in 8% of cases, 1% had breech presentation, 7% had a family history of developmental dysplasia and 7% had been swaddled. Additional congenital anomaly and torticollis were not detected at the physical examination of the babies. The risk factors were determined to be twin birth and female gender in the only baby who had developmental hip dysplasia (Type 2a). Conclusion: Developmental hip displasia is a significant public health concern in developing countries. Physical examination performed in conjunction with hip ultrasonography routinely in the neonatal period may contribute to the early diagnosis and treatment. (The Medical Bulletin of Haseki 2010; 48: 99-102)